How do you simplify {4 (3-7) + 12}^2 / (-4) -3^3 using PEMDAS?

2 Answers
Feb 17, 2017

The answer is -31.

Explanation:

Step 1: (4(3-7)+12)^2/-4-3^3
Step 2: (4*(-4)+12)^2/-4-27
Step 3: (-16+12)^2/-4-27
Step 4: (-4)^2/-4-27
Step 5: -4-27=-31

Feb 17, 2017

See the entire simplification process below:

Explanation:

First, we need to process the inner Parenthesis (P) containing (3 - 7) = -4:

{4 xx -4 + 12}^2/-4 - 3^3

Next, we can process the Multiplication (M) within the brackets or Parenthesis (P): 4 xx -4 = -16

{-16 + 12}^2/-4 - 3^3

Then we can process the Addition (A) within the brackets (P) {-16 + 12 = -4}

{-4}^2/-4 - 3^3

Next, we can process the Exponents (E): {-4}^2 = 16 and 3^3 = 27:

16/-4 - 27

The we can process the Division (D) - 16/-4 = -4:

-4 - 27

Now, we can complete the simplification by processing the Subtraction (S):

-4 -27 = -31